(untitled) (Eurasian Research Bulletin, 2022)
The study of body composition depending on age allows athletes of different ages to study the features of changes in the labile components of body weight. In the prepubertal period, there is a gradual and low increase in muscle mass, as well as a change in the volume of fat along the main border. A significant increase in muscle mass during puberty (especially in boys), a decrease in fat mass is characterized by a slight increase in boys and girls. This article, devoted to a review of the literature, is intended to study the significance of body composition indicators in junior and cadet athletes and currently informative methods for studying it